Characteristics of equatorial electrojet derived from Swarm satellites - Thomas, Neethal; Vichare, Geeta; Sinha, Ashwini K. (My University, 2017)
The vector magnetic field measurements from three satellite constellation, Swarm mission (Alpha ‘Swarm-A’, Bravo ‘Swarm-B’, and Charlie ‘Swarm-C’) during the quiet days (daily P Kp 6 10) of the years 2014–2015 are used to study the characteristic features of equatorial electrojet (EEJ). A program is developed to identify the EEJ signature in the X (northward) component of the magnetic field recorded by the satellite. An empirical model is fitted into the observed EEJ signatures separately for both the hemispheres, to obtain the parameters of electrojet current such as peak current density, total eastward current, the width of EEJ, position of the electrojet axis, etc. The magnetic field signatures of EEJ at different altitudes are then estimated. Swarm B and C are orbiting at different heights (separation 50 km) and during the month of April 2014, both the satellites were moving almost simultaneously over nearby longitudes. Therefore, we used those satellite passes to validate the methodology used in the present study. The magnetic field estimates at the location of Swarm-C obtained using the observations of Swarm B are compared with the actual observations of Swarm-C. A good correlation between the actual and the computed values (correlation coefficient = 0.98) authenticates the method of analysis. The altitudinal variation of the amplitude and the width of the EEJ signatures are also depicted. The ratio of the total eastward flowing forward to westward return currents is found to vary between 0.1 and 1.0. The forward and return current values in the northern hemisphere are found to be 0.5 to 2 times of those in the southern hemisphere, thereby indicating the hemispheric asymmetry. The latitudinal extents of the forward and return currents are found to have longitudinal dependence similar to that of the amplitude and the width of EEJ showing four peak structures. Local time dependence of EEJ parameters has also been investigated. In general, the results are found to be consistent with previous studies. In order to examine the existence of the EEJ associated meridional currents, we have estimated the vertical current density using combination of two satellites separated in longitude.
Keywords: Swarm magnetic field; EEJ current parameters; Equatorial electrojet currents; Equatorial electrojet